Determination of Brilink Cash Transfer Tariffs from a Sharia Economic Law Perspective - Yusrianti, Yusrianti; Hasriadi, Hasriadi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
The development of science and technology follows the pace of the development of muamalah activities, especially cash transfer activities via BRILink. The transactions carried out by several BRILink agents gave rise to problems that were outlined in the problem formulation, namely how to determine cash transfer rates for BRILink agents in Pakkanna Village, Tanasitolo District, Wajo Regency, as well as the perspective of Sharia economic law on determining cash transfer rates at BRILink. Therefore, this research aims to determine the mechanism for setting rates and whether the rates set by each agent are under Sharia economic law. This research uses a qualitative research method where data collection is carried out employing observation, visual analysis, and interviews with all BRILink agents in Pakkanna Village, Tanasitolo District, Wajo Regency. Based on the research results, it is known that transactions carried out between BRILink agents and customers use a wage-reward system. The tariff-setting system used by BRILink agents is a system set by the agent himself. According to the research conducted by the author, this wage system contract is legally permissible and valid because it is in line with Sharia economic law.